Іmplementation of mhGAP in Medical Students’ Education: An Overview of Opportunities and Challenges - Sodolevska, Валерія; Misak, Ілона (Psychosomatic Medicine and General Practice, 2025)
Introduction. Mental health is a crucial component of overall well-being, enabling individuals to cope with life’s challenges, realize their potential, study, work, and contribute to the development of society. It is an integral part of physical health that determines a person's ability to make decisions, build interpersonal relationships, and influence the social environment. Mental health is also recognized as a fundamental human right and a key factor in personal, social, and economic development. According to the World Health Organization (WHO), approximately 20% of the global population experiences mental health problems during their lifetime, significantly affecting their quality of life and level of productivity, thereby playing a vital role in ensuring effective, multidisciplinary medical care. [1] The Mental Health Gap Action Programme (mhGAP) is a flagship WHO initiative aimed at addressing the global shortage of mental health professionals, especially in low- and middle-income countries. It is designed to scale up services for the treatment of mental, neurological, and substance use (MNS) disorders. [2] Introducing mhGAP into the education of medical students in Ukraine is a promising step toward improving training quality and ensuring broader access to mental health care for the population. During their studies, medical students are constantly exposed to psychological and emotional stress, which has significantly increased under the conditions of full-scale war. This has led to a rise in emotional exhaustion, prolonged stress, and other signs of mental health deterioration, such as sleep disturbances, anxiety, loss of appetite, chronic tension, low mood, and depressive symptoms. In the absence of timely support, such states may develop into mental disorders or lead to professional burnout. Integrating mhGAP into the academic curriculum can enhance the quality of medical education and prepare future professionals to work with mental health, while also equipping them with self-help skills based on mhGAP case guidance. Objective. This article aims to analyze the opportunities and challenges of integrating mhGAP into the educational programs of Ukrainian medical universities and provide practical recommendations for effective implementation. Methods. The article is based on a review of literature related to the WHO Mental Health Action Programme and its implementation in the field of mental health, with a focus on international experiences and prospects for adapting the program to Ukrainian medical universities. Sources included WHO publications, peer-reviewed articles, official reports, and documents detailing mhGAP integration into medical education. In the course of analyzing evidence on the effectiveness of the mhGAP programme implementation, 2,621 scientific sources were reviewed. Of these, 162 publications reported confirmed positive outcomes. The main areas of implementation included training courses (59 publications), clinical application (49), scientific research (27), adaptation of the programme to local contexts (13), economic evaluations (7), and educational programmes (7). The majority of the reported results originated from African countries (40% of the studies) and the South-East Asia region. The data clearly demonstrate improvements in the level of knowledge, clinical skills, and competencies among participants of mhGAP programmes, as well as positive dynamics in the psychosocial well-being of patients who received care based on mhGAP approaches. Results. The literature review demonstrates that integrating mhGAP into educational programs positively impacts the preparation of future physicians. Numerous studies show that the use of interactive learning methods, simulation-based training, and modern technologies fosters deeper understanding of theoretical content and the development of practical skills in mental health. This improves the early identification and management of patients with mental disorders, which is essential for reducing the treatment gap and increasing the effectiveness of primary health care. The analysis also highlights that mhGAP-based modules help reduce stigma associated with mental disorders by increasing awareness and promoting more empathetic attitudes among future healthcare providers. However, the review identified several challenges in implementing the program, including limited financial resources, insufficient training of teaching staff, and the need to adapt academic curricula to the national healthcare system. Despite these barriers, studies from countries such as Pakistan, Tunisia, and Nigeria reveal the high potential of mhGAP to modernize medical education and enhance the quality of care. These successful cases show that such programs not only improve clinical competencies but also support the development of interdisciplinary collaboration in health systems. Conclusions. Integrating mhGAP into the curricula of Ukrainian medical universities offers promising opportunities for enhancing the training of future doctors. By incorporating modern approaches to teaching mental health, students not only acquire theoretical knowledge but also develop practical skills for early detection, diagnosis, and primary management of mental disorders. This fosters the formation of highly qualified specialists capable of effectively responding to the challenges of contemporary medicine. A major advantage is the potential to deliver timely care by embedding psychiatric competencies into primary healthcare. Equipping doctors with relevant knowledge and practical tools enables prompt response to mental health issues, which is especially important under resource constraints and increased pressure on specialized services. This can contribute not only to lowering the prevalence of mental disorders but also to improving patients’ quality of life. Future research should focus on long-term evaluations of mhGAP implementation, including assessments of changes in healthcare quality and the program's impact on intersectoral cooperation within the health system. Recommendations for university administrators and governmental institutions could serve as a vital foundation for ensuring sustainable reforms and the ongoing advancement of medical education in Ukraine.